Densest Columnar Structures of Hard Spheres from Sequential Deposition - CHAN, HO-KEI (My University, 2011)
The rich variety of densest columnar structures of identical hard spheres inside a cylinder can surprisingly be constructed from a simple and computationally fast sequential deposition of cylinder-touching spheres, if the cylinder-to-sphere diameter ratio D is within [1,2.7013]. This provides a direction for theoretically deriving all these densest structures and for constructing such densest packings with nano-, micro-, colloidal or charged particles, which all self-assemble like hard spheres.
PUBLISHED
Keywords: Condensed matter physics; Hard spheres